2017
DOI: 10.1080/10942912.2017.1357044
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality as affected by olive oil

Abstract: Various studies have investigated the effects of olive oil on semen quality and sperm physiology. This review systematically discusses and summarises the link between olive oil and semen quality. To achieve this contribution, we searched the PubMed, Scopus, Web of Science, and Google scholar databases for articles and reports published in English (as full articles or abstract only) from September 1975 through February 2017 using the key words "olive oil" and "sperm". Certain interrelated articles were also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Low SP levels of tyrosine, the precursor of thyroid hormones, were found to be associated with sperm maturation, acrosome reaction, and infertility [72][73][74][75]. Also, tyrosol has been associated with normal sperm physiology [76,77] and DNA integrity [78]. In general, our findings are in line with several studies that demonstrated the potential role of SP constituents in male infertility [65,66,[79][80][81].…”
Section: Discussionsupporting
confidence: 88%
“…Low SP levels of tyrosine, the precursor of thyroid hormones, were found to be associated with sperm maturation, acrosome reaction, and infertility [72][73][74][75]. Also, tyrosol has been associated with normal sperm physiology [76,77] and DNA integrity [78]. In general, our findings are in line with several studies that demonstrated the potential role of SP constituents in male infertility [65,66,[79][80][81].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, olive oil contains omega-3 polyunsaturated fatty acids [12] and has beneficial bioactive components (flavonoids and polyphenols) as bioactive organic molecules. These compounds have antimicrobial, antioxidant and anti-inflammatory properties [13]. The antioxidant status in the testes of rat were improved in term of increased TAC and decreased MDA level by olive leaves extract [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has beneficial bioactive components such as flavonoids (luteolin and apigenin), polyphenols (oleuropein, hydroxytyrosol and tyrosol) and squalene, as bioactive organic molecules. These compounds have antimicrobial, antioxidant and anti-inflammatory properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…The data clearly showed the highest significant (P ≤ 0.05) increase in fertility, hatching% and hatching weight in laying quail fed IOP up to 60 g/kg diet as compared to control. The significant effect of IOP diets on above mentioned parameters may be attributed to the rich of IOP with olive oil 6.8% Afsari et al (2014), which contains several potent bioactive compounds such as various natural antioxidants (oleuropein and tyrosol), tocopherol (Vitamin E), These compounds have been directly and indirectly linked to reproductive capability, as such interrelated with semen quality and sperm function through enhancing gonadal physiology, and thus increased reproductive performance (Banihani, 2017;Rafehi et al, 2012). In addition, utilization of IOP in laying Japanese quail nutrition enriched the eggs with unsaturated fatty acids and improved the egg quality (Abd El-Samee & Hashish, 2007), resulted in lower embryonic mortality level, higher hatching weight and hatching percentage.…”
Section: Fertility Embryonic Mortality Hatching % and Hatching Weightmentioning
confidence: 99%